Chromium-doped garnet solid electrolyte ceramic and preparation method thereof
By doping chromium-doped garnet solid electrolyte ceramics at the Zr site, the problem of insufficient ionic conductivity of existing garnet-type solid electrolytes is solved, and higher ionic conductivity is achieved, meeting the high energy density and safety performance needs of lithium batteries in electric vehicles and other fields.
Patent Information
- Application Number
- CN202510030302.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
AI Technical Summary
The ionic conductivity of existing garnet-type solid electrolytes is difficult to reach 10-3S/cm, and it cannot meet the high energy density and safety performance requirements of lithium batteries in electric vehicles and other fields.
The chromium-doped garnet solid electrolyte ceramic is prepared by doping chromium elements at the Zr site, with the chemical formula Li7+xLa3Zr2-xCrxO12, 0.05≤X≤0.5, and its ionic conductivity is improved.
The initial ionic conductivity of chrome-doped garnet solid electrolyte ceramics is 4.8×10-5S/cm, and it is as high as 1.1×10-3S/cm after exposure to air for 2 hours, which significantly improves the ionic conductivity.
Smart Images

Figure CN119822830A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of advanced ceramics and energy storage, and in particular relates to a chromium-doped garnet solid electrolyte ceramic and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are widely used in various electronic devices and mobile communications due to their high energy density, high operating voltage and long cycle life. The lithium batteries currently circulating in the market usually use liquid electrolytes. Liquid electrolytes have high lithium ion conductivity, but there are safety issues such as overcharging or short circuiting, easy leakage, corrosion, and high-temperature decomposition, which may cause fire or explosion, making them a safety hazard. In recent years, with the rapid development of electric vehicles and other fields, higher requirements have been placed on the battery life and safety performance of lithium batteries. Solid-state batteries have the characteristics of high energy density and high safety performance and have become a research hotspot. The performance of solid-state batteries depends on the development of solid-state electrolytes. At present, garnet-type solid electrolytes are considered to be one of the most promising solid-state electrolytes due to their high ionic conductivity, wide electrochemical window and good compatibility with the anode. However, the ionic conductivity of garnet electrolytes is currently difficult to reach 10 -3 S / cm, there is still a big gap compared with the electrolyte. Summary of the invention
[0003] In order to solve the above technical problems, the present invention proposes a chromium-doped garnet solid electrolyte ceramic and a preparation method thereof. The chromium-doped garnet solid electrolyte ceramic provided by the present invention has strong hygroscopicity and can improve the ionic conductivity of the solid electrolyte.
[0004] To achieve the above object, the present invention provides a chromium-doped garnet solid electrolyte ceramic, wherein the chromium-doped garnet solid electrolyte ceramic is composed of the elements lithium, lanthanum, zirconium, chromium and oxygen, and has a chemical formula of Li 7+ x Ln3Z 2-x Cr x O 12 , where 0.05≤X≤0.5.
[0005] The present invention also provides a method for preparing the chromium-doped garnet solid electrolyte ceramic, comprising the following steps:
[0006] (1) mixing a lithium source, a zirconium source, a lanthanum source and a chromium source, ball milling and drying to obtain a garnet precursor powder;
[0007] (2) taking the garnet precursor powder obtained in step (1), calcining it to obtain a chromium-doped garnet electrolyte powder;
[0008] (3) grinding the chromium-doped garnet electrolyte powder obtained in step (2), passing it through a 60-mesh sieve, and subjecting it to molding to obtain a chromium-doped garnet electrolyte blank;
[0009] (4) Taking the chromium-doped garnet electrolyte green body obtained in step (3), sintering it to obtain a chromium-doped garnet solid electrolyte ceramic.
[0010] Preferably, the lithium source in step (1) is lithium carbonate and / or lithium hydroxide, the zirconium source in step (1) is zirconium oxide and / or zirconium oxynitrate, the lanthanum source in step (1) is lanthanum oxide, and the chromium source in step (1) is chromium oxide.
[0011] Preferably, the purity of the lithium source, zirconium source, lanthanum source and chromium source is above 99wt%.
[0012] Preferably, the ball milling in step (1) is wet milling, the dispersant for the ball milling in step (1) is isopropanol and / or ethanol, the medium for the ball milling is zirconium balls, the rotation speed of the ball mill is 400-500 r / min, and the ball milling time is 6-12 h.
[0013] Preferably, in step (1), the mass ratio of the total mass of the lithium source, zirconium source, lanthanum source and chromium source, the dispersant and the ball milling medium is 1:1:6-10.
[0014] Preferably, the ball milling in step (1) is carried out in a polytetrafluoroethylene ball mill, and the ball milling adopts intermittent alternating ball milling, specifically: forward ball milling for 30 minutes, intermittent for 5 minutes, and reverse ball milling for 30 minutes.
[0015] Preferably, the drying temperature in step (1) is 75-85° C., and the drying time is 5-7 hours.
[0016] Preferably, the calcination temperature in step (2) is 750-900°C, the calcination heating rate is 3-5°C / min, the calcination time is 5-12h, and the calcination is carried out in an air atmosphere; the diameter of the chromium-doped garnet electrolyte powder in step (2) is 5-20 μm. The color of the chromium-doped garnet electrolyte powder changes from yellow to fluorescent green as the doping amount increases.
[0017] Preferably, the calcination in step (2) is carried out in a magnesium oxide crucible in a muffle furnace, and after the calcination, the mixture is cooled to room temperature at a cooling rate of 1 to 3° C. / min.
[0018] Preferably, the molding process in step (3) is cold isostatic pressing, the molding process pressure is 112 to 338 MPa, the molding process temperature is 20 to 25° C., and the molding process time is 1 to 3 min; the diameter of the chromium-doped garnet electrolyte blank in step (3) is 13 mm.
[0019] Preferably, the molding process in step (3) is carried out in a mold.
[0020] Preferably, in step (4), the sintering temperature is 1200-1250° C., the sintering heating rate is 2-10° C. / min, the sintering time is 0.5-6 h, and the sintering is carried out in an air atmosphere.
[0021] Preferably, the sintering in step (4) is carried out in a magnesium oxide crucible of a muffle furnace, and during the sintering process, a layer of chromium-doped garnet electrolyte powder is laid on the bottom of the magnesium oxide crucible, and the surface of the chromium-doped garnet electrolyte blank is covered with chromium-doped garnet electrolyte powder to prevent adhesion; after the sintering, the temperature is lowered to room temperature at a cooling rate of 1 to 3°C / min. During the sintering process, the chromium-doped garnet electrolyte particles grow and the ceramic is densified, and the color of the chromium-doped garnet solid electrolyte ceramic is yellow to fluorescent green.
[0022] Compared with the prior art, the present invention has the following advantages and technical effects:
[0023] The present invention provides a chromium-doped garnet solid electrolyte ceramic and a preparation method thereof, the chemical formula of which is Li 7+ x Ln3Z 2-x Cr x O 12 The present invention is based on Li7La3Zr2O 12 The chromium-doped garnet solid electrolyte ceramics are prepared by replacing Zr atoms at the Zr site of (LLZO), and the substitution ratio is (0.05≤x≤0.5). The chromium-doped garnet solid electrolyte is prepared by doping chromium elements at the Zr site, which can absorb moisture in the air to promote the migration of lithium ions and improve the ionic conductivity. The results show that the initial ionic conductivity of the chromium-doped garnet solid electrolyte ceramics provided by the present invention is 4.8×10 -5 S / cm, after being placed in air for 2 hours, the ionic conductivity reached 1.1×10 -3 S / cm. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 2 are XRD patterns of chromium-doped garnet solid electrolyte ceramics, wherein (a) is the chromium-doped garnet solid electrolyte ceramic of Example 1, and (b) is the chromium-doped garnet solid electrolyte ceramic of Example 2;
[0026] Figure 2 The SEM images of chromium-doped garnet solid electrolyte ceramics, wherein (a) is the chromium-doped garnet solid electrolyte ceramic of Example 1, and (b) is the chromium-doped garnet solid electrolyte ceramic of Example 2, and the scale is 50.0 μm;
[0027] Figure 3 1 and 2 are EIS graphs of the chromium-doped garnet solid electrolyte ceramics initially and after being placed in air, wherein (a) is the chromium-doped garnet solid electrolyte ceramics of Example 1, and (b) is the chromium-doped garnet solid electrolyte ceramics of Example 2. DETAILED DESCRIPTION
[0028] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0029] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0030] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0031] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0032] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0033] Example 1
[0034] (1) Weigh 2.373 g of lithium carbonate (10 wt% excess lithium carbonate to compensate for the volatilization of lithium at high temperature), 3.912 g of lanthanum oxide, 1.676 g of zirconium oxide and 0.182 g of chromium oxide, and pour the above raw materials into a polytetrafluoroethylene ball mill; add 68 g of zirconium balls and 20 mL of isopropanol according to the mass ratio of raw materials, isopropanol and ball milling medium zirconium balls of 1:1:8; ball mill on a planetary ball mill (ball milling adopts intermittent alternating ball milling, specifically: forward ball milling for 30 min, intermittent for 5 min, and reverse ball milling for 30 min), the speed is 500 r / min, and the time is 12 h; put the ball-milled slurry into an 80°C oven and dry for 6 h to obtain a chromium-doped garnet precursor powder;
[0035] (2) placing the chromium-doped garnet precursor powder into a magnesium oxide crucible, heating the mixture to 900° C. at a heating rate of 5° C. / min in a muffle furnace, calcining the mixture for 5 h in an air atmosphere, and cooling the mixture to room temperature at a rate of 2° C. / min to obtain a chromium-doped garnet electrolyte powder;
[0036] (3) pouring the chromium-doped garnet electrolyte powder into an agate mortar and grinding it evenly to pass through a 60-mesh sieve, weighing 500 mg of the powder and pouring it into a mold with an inner diameter of 13 mm, and maintaining it at 20° C. and a pressure of 225 MPa for 3 minutes to obtain a chromium-doped garnet electrolyte blank;
[0037] (4) The chromium-doped garnet electrolyte blank is placed in a magnesium oxide crucible, the blank is covered with chromium-doped garnet electrolyte powder, the temperature is increased to 1200°C in a muffle furnace at a heating rate of 5°C / min, sintered in an air atmosphere for 5 hours, and cooled to room temperature at a rate of 2°C / min to obtain a chromium-doped garnet solid electrolyte ceramic. The chromium-doped garnet solid electrolyte ceramic (Li 7.35 Ln3Z 1.65 Cr 0.35 O 12 ) has an ionic conductivity of 1.38×10 -4 S / cm.
[0038] The prepared chromium-doped garnet solid electrolyte ceramic was exposed to air for 2 hours (relative humidity 45%, temperature is room temperature), and the impedance change of the chromium-doped garnet solid electrolyte ceramic was tested using an electrochemical workstation.
[0039] Example 2
[0040] (1) Weigh 2.404 g lithium carbonate (10 wt% excess lithium carbonate to compensate for the volatilization of lithium at high temperature), 3.912 g lanthanum oxide, 1.576 g zirconium oxide and 0.244 g chromium oxide, and pour the above raw materials into a polytetrafluoroethylene ball mill; add 68 g zirconium balls and 20 mL isopropanol according to the mass ratio of raw materials, isopropanol and ball milling medium zirconium balls of 1:1:8; ball mill on a planetary ball mill (ball milling adopts intermittent alternating ball milling, specifically: forward ball milling for 30 min, intermittent for 5 min, and reverse ball milling for 30 min), the speed is 400 r / min, and the time is 12 h; put the ball-milled slurry into an 80°C oven and dry for 6 h to obtain a chromium-doped garnet precursor powder;
[0041] (2) placing the chromium-doped garnet precursor powder into a magnesium oxide crucible, heating the mixture to 900° C. at a heating rate of 5° C. / min in a muffle furnace, calcining the mixture in an air atmosphere for 12 h, and cooling the mixture to room temperature at a rate of 2° C. / min to obtain a chromium-doped garnet electrolyte powder;
[0042] (3) pouring the chromium-doped garnet electrolyte powder into an agate mortar and grinding it evenly to pass through a 60-mesh sieve, weighing 500 mg of the powder and pouring it into a mold with an inner diameter of 13 mm, and maintaining it at 25° C. and a pressure of 338 MPa for 3 minutes to obtain a chromium-doped garnet electrolyte blank;
[0043] (4) The chromium-doped garnet electrolyte blank is placed in a magnesium oxide crucible, the blank is covered with chromium-doped garnet electrolyte powder, the temperature is increased to 1250°C in a muffle furnace at a heating rate of 5°C / min, sintered in an air atmosphere for 6 hours, and cooled to room temperature at a rate of 2°C / min to obtain a chromium-doped garnet solid electrolyte ceramic. The chromium-doped garnet solid electrolyte ceramic (Li 7.4 Ln3Z 1.6 Cr 0.4 O 12 ) has an ionic conductivity of 1.1×10 -3 S / cm.
[0044] The prepared chromium-doped garnet solid electrolyte ceramic was exposed to air for 2 hours (relative humidity 45%, temperature is room temperature), and the impedance change of the chromium-doped garnet solid electrolyte ceramic was tested using an electrochemical workstation.
[0045] Experimental example
[0046] Test results of impedance change of chromium-doped garnet solid electrolyte ceramics
[0047] like Figure 1 As shown, it is the XRD pattern of the chromium-doped garnet solid electrolyte ceramic in Example 1 and Example 2. Figure 1 (a) and Figure 1It can be seen from (b) that the chromium-doped garnet solid electrolyte ceramic prepared in Example 1 is a tetragonal garnet phase, and the chromium-doped garnet solid electrolyte ceramic prepared in Example 2 is a cubic garnet phase.
[0048] like Figure 2 As shown, it is the SEM picture of the chromium-doped garnet solid electrolyte ceramic in Example 1 and Example 2. Figure 2 (a) and Figure 2 As can be seen in (b), the chromium-doped garnet solid electrolyte ceramics prepared in Example 1 and Example 2 both have a layered structure.
[0049] like Figure 3 As shown, the initial and 2h EIS graphs of the chromium-doped garnet solid electrolyte ceramics in Example 1 and Example 2 are shown. Figure 3 (a) and Figure 3 As can be seen in (b), the impedance of the chromium-doped garnet solid electrolyte ceramics prepared in Example 1 and Example 2 dropped significantly after being placed in air for 2 hours.
[0050] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A chromium-doped garnet solid electrolyte ceramic, characterized in that: The chromium-doped garnet solid electrolyte ceramic is composed of lithium, lanthanum, zirconium, chromium and oxygen, and has a general chemical formula of Li 7+x Ln3Z 2-x Cr x O 12 , where 0.05≤X≤0.
5.
2. The method for preparing the chromium-doped garnet solid electrolyte ceramic according to claim 1, characterized in that: The following steps are involved: (1) mixing a lithium source, a zirconium source, a lanthanum source and a chromium source, ball milling and drying to obtain a garnet precursor powder; (2) taking the garnet precursor powder obtained in step (1), calcining it to obtain a chromium-doped garnet electrolyte powder; (3) grinding the chromium-doped garnet electrolyte powder obtained in step (2), passing it through a 60-mesh sieve, and subjecting it to molding to obtain a chromium-doped garnet electrolyte blank; (4) Taking the chromium-doped garnet electrolyte green body obtained in step (3), sintering it to obtain a chromium-doped garnet solid electrolyte ceramic.
3. The preparation method according to claim 2, characterized in that: The lithium source in step (1) is lithium carbonate and / or lithium hydroxide, the zirconium source in step (1) is zirconium oxide and / or zirconium oxynitrate, the lanthanum source in step (1) is lanthanum oxide, and the chromium source in step (1) is chromium oxide.
4. The preparation method according to claim 2, characterized in that: In step (1), the dispersant for ball milling is isopropanol and / or ethanol, the medium for ball milling is zirconium balls, the rotation speed of the ball mill is 400-500 r / min, and the ball milling time is 6-12 h.
5. The preparation method according to claim 4, characterized in that: In step (1), the mass ratio of the total mass of the lithium source, the zirconium source, the lanthanum source and the chromium source, the dispersant and the ball milling medium is 1:1:6-10.
6. The preparation method according to claim 2, characterized in that: The drying temperature in step (1) is 75-85° C., and the drying time is 5-7 hours.
7. The preparation method according to claim 2, characterized in that: The calcination temperature in step (2) is 750-900° C., the calcination heating rate is 3-5° C. / min, the calcination time is 5-12 hours, and the calcination is carried out in an air atmosphere; the diameter of the chromium-doped garnet electrolyte powder in step (2) is 5-20 μm.
8. The preparation method according to claim 2, characterized in that: The molding process in step (3) is cold isostatic pressing, the molding process pressure is 112-338 MPa, the molding process temperature is 20-25° C., and the molding process time is 1-3 min; the diameter of the chromium-doped garnet electrolyte blank in step (3) is 13 mm.
9. The preparation method according to claim 2, characterized in that: In step (4), the sintering temperature is 1200-1250° C., the sintering heating rate is 2-10° C. / min, the sintering time is 0.5-6 h, and the sintering is carried out in an air atmosphere.